Investigation of vanadium–sodium silicate glasses using XANES spectroscopy - Faiz, M. (2020)
Abstract X-ray absorption near edge structure spectroscopy has been used to investigate the electronic and atomic structure of (V2O5)x(Na2O)0.30(SiO2)0.70−x (x < 0.1) glasses obtained by melt-quench technique. The results show no sign of metallic clustering of V atoms, but mixed oxidation states (+4 and +5) of V and strong V3d–O2p hybridization in the glasses. Detailed analysis has revealed that the glass samples contain about 15% V4+ and 85% V5+ and the ligand-field splitting is about 1.6 eV. © 2006 Elsevier B.V. All rights reserved. Keywords: XANES; Vanadium–sodium silicate glasses; V L2,3 edges; O K edge